Pemberdayaan Masyarakat Nelayan melalui Pengembangan Perikanan Tangkap di Desa Majakerta, Indramayu, Jawa Barat - Roisul Ma’arif; . Zulkarnain; Thomas Nugroho; . Sulistiono (Institut Pertanian Bogor, 2016)
Majakerta is one of the village in Indramayu which has high potential of capture fishery resources. Community empowerment through capture fishery had been done for two years and two months, since 2011-2013. The activity focused on two groups consisting of big group of fishermen (boat size more than 5 GT, 19 people) and small group one (boat size 2-5 GT, 58 people). Objective of the activity was to increase skill and knowledge of the fishermen, as a base to improve their income. From the result of activity, it was known that fishermen could increase their knowledge, skill, and income. Nevertheless, they still need assistance more intensively.